1993
DOI: 10.1080/14640749308401048
|View full text |Cite
|
Sign up to set email alerts
|

Boundaries of Separability between Melody and Rhythm in Music Discrimination: A Neuropsychological Perspective

Abstract: The detailed study of a patient who suffered from a severe amelodia without arhythmia as a consequence of bilateral temporal lobe damage revealed that the processing of melodic information is at least partially separable from the processing of rhythmic information. This dissociation was replicated across different sets of material, was supported by the presence of a reversed association, and was maintained in conditions that promote integration in the normal brain. These results argue against the view that mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
100
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 40 publications
8
100
0
2
Order By: Relevance
“…Peretz [29] reported that two right hemisphere damaged patients showed a selective deficit in the processing of pitch, while a reverse pattern of selective deficit of the temporal dimension was found in two left brain damaged patients. Other single case studies have also demonstrated selective impairment of one or the other dimension [13,24,30,31], and other studies in the field of cognitive psychology support the hypothesis of independence [15,26,28].…”
Section: Introductionmentioning
confidence: 72%
“…Peretz [29] reported that two right hemisphere damaged patients showed a selective deficit in the processing of pitch, while a reverse pattern of selective deficit of the temporal dimension was found in two left brain damaged patients. Other single case studies have also demonstrated selective impairment of one or the other dimension [13,24,30,31], and other studies in the field of cognitive psychology support the hypothesis of independence [15,26,28].…”
Section: Introductionmentioning
confidence: 72%
“…Isolated deficits of 'amelodia' and arrhythmia have been reported in the amusia literature for perceptual, productive, and musical reading tasks [4,13,30,37,38,[40][41][42]62]. Separate cognitive representations of melody and rhythm have also been proposed in the developmental [62,63] and normal adult literature [43,60,62], supporting the general applicability of this distinction.…”
Section: Introductionmentioning
confidence: 82%
“…Neuropsychological data suggest that these dimensions are not always tightly bound. Amusicsstroke patients or neurologically intact individuals with pronounced impairments on tasks requiring fine-grained pitch judgments-show better performance, sometimes even on par with control listeners, on temporal judgments, relative to pitch judgments, thereby indicating that at least in such individuals, the neural substrates supporting temporal and pitch judgments differ (Ayotte, Peretz, & Hyde, 2002;Hyde & Peretz, 2004;Peretz et al, 2002;Peretz & Kolinsky, 1993). It is, therefore, not surprising that mental images formed on each dimension can show different tuning characteristics, even if listeners are instructed to imagine objects in which these dimensions are integrated-for example, the notes of a melody.…”
Section: Discussionmentioning
confidence: 99%